Diversity of vascular plant communities along a disturbance gradient in a central mid-hill community forest of Nepal - Baral, SK; Katzensteiner, K (Banko Janakari, 2009)
The ‘Community Forestry Program' has been considered successful in improving the environmental situation in the hills of Nepal by enhancing the vegetation coverage of degraded sites and by improving the supply of forest products to farmers. The restoration measures are considered sustainable if the ecosystems are self-supporting and resilient against perturbation. A community forest (CF) in the mid-hills of Nepal has been assessed for restoration success based on the comparison of vegetation structure and species diversity along a disturbance gradient, using a semi-protected natural forest as a reference site. In general, the community forest management (CFM) was able to re-establish forests on formerly severely degraded sites. Forest operations carried out during CFM have altered plant community composition, species richness and distribution, age class distribution of trees and vegetation structure. As a result, the CF was being transformed into a less diverse regular forest although the overall vascular plant diversity was retained with sufficient niches within the understorey vegetation. Keywords: Central mid-hills, community forest, disturbance regimes, Nepal, plant diversity doi: 10.3126/banko.v19i1.2176 Banko Janakari, Vol. 19, No. 1, 3-10